The Prevalence of Undiagnosed Age-Related Sight-Threatening Diseases in Self-Proclaimed Healthy Individuals. (7th November 2020) - Lemmens, Sophie; Barbosa Breda, João; Van Keer, Karel; Jacobs, Tine; Van Landeghem, Ruben; De Boever, Patrick; Stalmans, Ingeborg
Abstract : Background . Age-related conditions such as glaucoma, age-related macular degeneration, diabetic retinopathy, and cataract have become the major cause of visual impairment and blindness in high-income countries. The aim of the current study is to investigate the prevalence of these eye diseases in a cohort of self-proclaimed healthy elderly and thus get a rough estimation of the prevalence of undiagnosed age-related eye conditions in the Belgian population. Methods . Individuals aged 55 and older without ophthalmological complaints were asked to fill in a general medical questionnaire and underwent an ophthalmological examination, which included a biomicroscopic examination, intraocular pressure measurement, axial length measurement, and acquisition of fundus pictures and optical coherence tomography scans. Information regarding follow-up was collected in those who received the advice of referral to an ophthalmologist or the advice to have more frequent follow-up visits, based on their study evaluation. Results . The cohort included 102 people and comprised 46% men (median age 70 years, range 57–85 years). Referral for additional examinations was made in 26 participants (25%). The advice to have more regular follow-up ophthalmologist visits was given to nine additional participants (9%). No significant correlations between baseline characteristics and the need for referral could be identified. Follow-up information was available for 25 out of 26 referred volunteers. Out of these, four underwent a therapeutic intervention based on study referral, up until 18 months after study participation. All four interventions took place in the age group 65–74 years. Conclusions . This study shows that, even in an elderly population with self-proclaimed healthy eyes and good general health, a significant proportion of subjects showed ocular findings that need regular follow-up and/or intervention. The frequency of prior ophthalmological examinations does not seem to be relevant to this proportion, meaning that everyone above 55 years old needs a routine ophthalmological evaluation.